Lily the rain forest fairy - Meadows, Daisy (Meadows, Daisy. Earth fairies, 2014)
"Lily the Rain forest Fairy whisks the girls away to a tropical forest to find her wand. Lily needs her wand to save the rainforest-and to get Rachel and Kirsty home safe again" -- From amazon.com.